2021
DOI: 10.1111/echo.15096
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular‐arterial coupling – A new perspective for right ventricle evaluation in heart failure patients undergoing cardiac resynchronization therapy

Abstract: Background Right ventricular – arterial (RV‐PA) coupling can be estimated by echocardiography using the ratio between (TAPSE) and pulmonary arterial systolic pressure (PASP). TAPSE/PASP ratio proved to be a prognostic parameter in patients with heart failure and reduced ejection fraction (HFrEF). Objective To evaluate the significance of RV‐PA coupling in patients with HFrEF undergoing cardiac resynchronization therapy (CRT). Methods Patients undergoing CRT in our center between January 2017 and November 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In a study of 54 CRT recipients, Deaconu et al . demonstrated that the TAPSE/PASP ratio was linked to both CRT response (defined as ≥15% reduction in LV end‐systolic volume) as well as cardiovascular events 23 . Using a different definition (≥5% improvement in LVEF), Bragança et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 54 CRT recipients, Deaconu et al . demonstrated that the TAPSE/PASP ratio was linked to both CRT response (defined as ≥15% reduction in LV end‐systolic volume) as well as cardiovascular events 23 . Using a different definition (≥5% improvement in LVEF), Bragança et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 54 CRT recipients, Deaconu et al demonstrated that the TAPSE/PASP ratio was linked to both CRT response (defined as ≥15% reduction in LV end-systolic volume) as well as cardiovascular events. 23 Using a different definition (≥5% improvement in LVEF), Bragança et al also found the TAPSE/PASP ratio to be associated with CRT response. 24 The current study expands on these results by demonstrating a strong, independent link between the TAPSE/PASP ratio and long-term outcome in a large, unselected cohort of CRT recipients.…”
Section: Non-invasive Estimation Of Right Ventricular-pulmonary Arter...mentioning
confidence: 99%
“…74 Several recent studies show that the TAPSE/PASP ratio can serve as a predictive tool to assess a patient's potential response to CRT. 38,75 Low TAPSE/PASP was associated with a greater likelihood of cardiac events and an inferior response to CRT. 76 TAPSE/PASP gives considerable clinical utility to overtime surveillance of patients with HFrEF after CRT.…”
Section: Hf With Reduced Ejection Fractionmentioning
confidence: 98%
“…Patients with HFrEF can benefit from cardiac resynchronization therapy (CRT) 74 . Several recent studies show that the TAPSE/PASP ratio can serve as a predictive tool to assess a patient's potential response to CRT 38,75 . Low TAPSE/PASP was associated with a greater likelihood of cardiac events and an inferior response to CRT 76 .…”
Section: Tricuspid Annular Plane Systolic Excursion/pulmonary Artery ...mentioning
confidence: 99%
“…In a cohort of 54 patients with HfrEF undergoing cardiac resynchronization therapy, it was demonstrated that TAPSE/PASP displayed good sensitivity (90%) and specificity (81.8%) for predicting the response to cardiac resynchronization therapy. Moreover, a lower TAPSE/PASP ratio was associated with a higher incidence of adverse cardiovascular events during the follow-up [ 94 ]. Hence, these findings suggested that the TAPSE/PASP ratio may become a standard echocardiographic evaluation parameter for HfrEF patients undergoing cardiac resynchronization therapy.…”
Section: Clinical Applications Of Rv-pa Couplingmentioning
confidence: 99%